Land reforms and agricultural development - "Sain, K." (New Delhi, 1982)
In recent years there has been much dispute on the subject of effectiveness of land reforms on agricultural development in different countries of the world. The polemic still remains unsettled. A sincere attempt has been made to analyse available literature on the subject and to gather first-hand knowledge through field investigation. The book also deals with some technical matters relating to agrarian regeneration and farm price policy. These lead to the observation, inter alia, that land reforms have significant contribution to agricultural development, at any rate when associated with complementary measures. The scrupulous appraisal and presentation of facts make this book invaluable to legislators, planners, policy makers, students and researchers in Agricultural Economics.
Keywords: Land reform India